Perkembangan Desain Produk Kerajinan Perak Koto Gadang sebagai Potensi Daerah di Sumatera Barat - Yensharti, Yensharti; Afriwan, Hendra (SPACEPRO: Product Design Jurnal, 2023)
Silver Koto Gadang is an attempt to descend from their ancestors who have inherited from their parents, prosperity, children, and grandchildren as well as silver craftsmanship skills. The silver crafts owned by Koto Gadang are one of the elements that are incorporated into the customs of the community such as jewelry, curtain clothes, customary clothing and including the weddings of the region. The Koto Gadang community still uses the manual technique because the craftsmen maintain the custody of their products, in addition to preserving the historical value that the technique inherited downwards. This paper focuses more on library research using data analysis and qualitative analysis. Silver Koto Gadang, is an undertaking where all the communities there have skills as silver craftsmen, and one of these Nagari Koto gadang makes silver jewellery as a social culture in social customs. Seeing the potential of silver crafts from Koto Gadang is a great opportunity for Nagari Kato Gadang as the center of art crafts silver that is located in the village of Koto IV, Koto Gadan Kabupatean Agam which is chosen as the centre of silversmiths.Keywords: Silverwork; Koto Gadang; Design: Potensial.